Achieving Harmonious Employment Relationship - Anggraeni, Ade Irma (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
In the context of managing talented employees, psychological contracts play a role in encouraging employees to develop sustainable knowledge sharing capabilities. Employees who are committed to their personal career development tend to be proactive in sharing knowledge to improve their professionalism. The effectiveness of the psychological contract is determined by the strategic components within it. Based on the social exchange paradigm, the psychological contract provides an opportunity for organisations to build social capital and sustainable competitiveness through organizational citizenship behaviour. This refers to the behaviour of employees in contributing more to the effectiveness of organisational functions, not listed in the job description but useful for the long-term success of the organisation. This study recommends that important aspects of building a psychological contract include a conducive work environment, employee career development and productive working relationships based on trust.